Did the Accounting for Goodwill Create a Bubble? - Bingyi Chen; Ariel Markelevich; Irene Guannan Wang (The Indonesian Journal of Accounting Research, 2021)
This article investigates the accounting standards changes related to business acquisitions and the impact of those changes on the reported goodwill in the past 50 years. We observe that the amount of goodwill on companies’ balance sheets steadily increased before 2001 but has risen to new levels with the adoption of SFAS 141. Goodwill is now equal to about 30 percent of companies’ net assets compared to only about 7 percent in the 1980s. We examine whether the increased levels of goodwill could have resulted from changes in accounting standards. Specifically, we investigate the impacts of accounting regulations on goodwill reporting under three different regimes: APB 16 and 17, SFAS 141 and 142, and SFAS 141(R). We find that the increase in the reported value of goodwill is not a result of an increase in public companies’ acquisitions, as those have actually decreased over time. Further, the increase overlaps with the changes to the accounting for goodwill and the switch from goodwill amortization to impairment. Our findings are timely and important because the Financial Accounting Standards Board (FASB) has a concurrent project revisiting Identifiable Intangible Assets and Subsequent Accounting for Goodwill (FASB 2020). Our evidence urges caution in the reintroduction of goodwill amortization proposed by FASB, as the level of goodwill has increased dramatically despite FASB’s intentions to improve the quality of goodwill accounting and curtail management’s goodwill manipulation.